A case report on the successful perioperative management of hepatectomy for hepatocellular carcinoma in a patient with von Willebrand disease. (2018) - Sato, Koki; Kuroda, Shintaro; Kobayashi, Tsuyoshi; Shimizu, Seiichi; Ohira, Masahiro; Tahara, Hiroyuki; Ide, Kentaro; Fujii, Teruhisa; Ohdan, Hideki
Highlights: Although von Willebrand disease (VWD) is a common inherited bleeding disease, only 1 case of hepatectomy in a patient with VWD has been described. Perioperative hemostatic management is important especially in patients with VWD undergoing surgery because of the dysfunction of the platelet and destabilization of the blood clotting factor VIII. The patient was successfully treated by administering factor VIII/von Willebrand factor concentrate and by measuring activated partial thromboplastin time as an index for perioperative hemostatic management. Abstract: Introduction: Although von Willebrand disease (VWD) is a common inherited bleeding disorder, very few cases of surgery in patients with VWD have been reported. Presentation of case: A 77-year-old man was referred to our hospital for treatment of hepatocellular carcinoma (HCC) based on type C chronic hepatitis. He had also been treated for VWD in the hematology department of another hospital. Partial hepatectomy was performed with the administration of factor VIII/von Willebrand factor concentrate just before and after the operation. The perioperative course was uneventful, and the patient was discharged 12 days after surgery. Discussion: VWD causes dysfunction of the platelet and destabilization of the blood clotting factor VIII. The patient was successfully treated with measurement of activated partial thromboplastin time (APTT) as an index for the management of hemostasis. Conclusion: This report describes a rare case of a successful perioperative management of hepatectomy in a patient with VWD.